Nature positive rhetoric, risk and reality: sector-scale political ecology at CBD COP16 - Buckley, Ralf C.; Liddon, Meisha; Underdahl, Sonya; Zhang, Zoë Jiabo; Cooper, Mary Ann; Chauvenet, Alienor L.M.; Zhong, Linsheng (Springer Nature, 2025)
We analyse political manoeuvres by global tourism industry associations, and responses by conservation organisations, that create new risks to biodiversity. There are a few tourism enterprises that make net positive contributions to conservation. Nature positive terms, however, are being used for marketing greenwash, to delay and avoid environmental fees and regulations, and to lobby for land grabs in public protected areas.